Hypoxemic Bronchiolitis Related to Major Histocompatibility Class II Deficiency - S. Hammami; H. Besbès; S. Hadded; K. Lajmi; L. Ghédira; Ch. B. Meriem; M. N. Guediche (Case Reports in Medicine)
Major histocompatibility complex class II expression deficiency is an autosomal recessive primary combined immunodeficiency. The prevalence of this deficiency is the highest in Mediterranean areas, especially North Africa. Early diagnosis is essential due to high mortality in the first 2 years of life. Prognosis is very poor when bone marrow transplantation cannot be performed. We report the case of an infant with major histocompatibility complex class II expression deficiency revealed by hypoxemic bronchiolitis due to Pneumocystis jiroveci.